APLIKASI PUPUK NITROGEN+KALIUM MELALUI TANAH DAN DAUN TERHADAP PRODUKSI PROTEIN DAN ANTOSIANIN PUCUK LAYAK JUAL KOLESOM (Talinum triangulare (Jacq.) Willd) - Hilda Susanti; Sandra Arifin Aziz; Maya Melati; Slamet Susanto (EnviroScienteae, 2013)
The experiment was conducted in Leuwikopo, Dramaga, Bogor, Indonesia from October until December 2010  to study the effect of soil and foliar applications of nitrogen+potassium fertilizer on waterleaf shoot (Talinum triangulare (Jacq.) Willd) protein and anthocyanin production. A randomized complete block design was used with 3 replications and 4 treatments. The treatments were different rates of N+K for soil application with or without foliar application, they were 100% N+K rates of soil application (150 kg urea + 150 kg KCl/ha); 100, 75, and 50% N+K rates of soil application added with foliar application of 0.2% urea and 0.1% KCl.  Fertilizers were applied on soil on 0, 30, and 60 days after planting, while foliar applications were conducted on 15, 30, 45, and 60 days after planting.  The result showed that the highest protein and anthocyanin production of waterleaf shoot for 75 days were produced by 100% soil application of N+K; protein production was 16,98 g/plant while anthocyanin production was 170,27µmol/plant.